Microhistorical Description of Violence in the Cristero Rebellion of Coalcomán (1927-1928). Luis Navarro Origel, a Violent Intellectual? (Palimpsesto, 2017)
Ninety years after of the beginning of the Cristero rebellion of Coalcomán (Michoacán, Mexico), this article review the first year of the increase of violence (1927-1928). The research andÂ  microhistorical analysis are based on the revisionist debate -with a strong emphasis on the “new” German sociology- about the notion of violence and the place,Â  violent intellectuals in contexts of collective violence, and spaces away from state interference. The revision of the figure of Luis Navarro Origel is analyzed as a productive case study for this problem. The microhistorical description of the violence will illuminate the process of its increase, its dynamics, its contexts, its variables, its relevant actors like those intellectuals involved in the action and narration.
Keywords: Mexico post-revolutionary; Cristero rebellion; violence; intellectuals